Identifikasi Single Nucleotide Polymorphism (SNP) Gen pvmdr1 pada Penderita Malaria Vivaks di Minahasa Tenggara (Sulawesi Utara) - Salwati, Ervi; Handayani, Sarwo; Jekti, Rabea Pangerti (Jurnal Biotek Medisiana Indonesia, 2014)
Parasite resistance to antimalarial drugs is an obstacle to malaria elimination. In Plasmodium vivax, up to now, a marker to distinguish between resistant and susceptible is no available yet. Identify Single Nucleotide Polymorphisms (SNP) in P. vivax for multidrug resistance (pvmdr1)is potential approach due to pvmdr1 gene is orthologous to the pfmdr1 of P.falciparum, have been related to multidrug resistance. The purpose of this study was to identify SNPs/mutations on pvmdr1 gene of malaria vivax patients who came to the Primary Healthe Centers, Touluaan and Tombatu Minahasa Tenggara (North Sulawesi).Blood samples and slide of blood smears were collected from patients who infected with P.vivax or mixed infection of P.vivax and P.falciparum. After the species were cross checked by certified microscopist then confirmed by PCR, SNP identification were performed by sequencing technique. Only 83 of 99 recruited subjects were included inclution criteria. Sequensing result showed that 59 of 83 subjects were analysed to identify the SNP. We found 5 nonsynonymous SNPs, namely at the point G698S, M908L, Y976F, L1076F, and K1261E.Key words: Plasmodium vivax, Single Nucletide Polymorphism, Gen pvmdr1, MutationÂ AbstrakResistensi parasit terhadap obat anti malaria merupakan salah satu kendala untuk eliminasi malaria. Pada Plasmodium vivax, sampai saat ini penanda parasit yang resisten dengan yang masih sensitif belum tersedia. Identifikasi Single Nucleotide (SNP) gen pvmdr1 P.vivax multidrug resistance (pvmdr1) merupakan pendekatan yang potensial, karena gen pvmdr1 ortolog dengan gen pfmdr1 P. falciparum yang telah terbukti berkaitan dengan multidrug resisten. Tujuan penelitian adalah untuk mengidentifikasi SNP/mutasi pada gen pvmdr1 dari pasien malaria vivax yang berobat ke Puskesmas Touluaan dan Tombatu di Minahasa Tenggara (Sulut). Sampel darah dan sediaan apusan darah tebal dan tipis dikumpulkan dari pasien yang terinfeksi P.vivax atau infeksi campuran P.vivax dan P.falciparum. Setelah spesies dicek ulang oleh mikroskopis pusat dan dikonfirmasi dengan teknik PCR, dilanjutkan dengan identifikasi SNP dengan teknik sekuensing Dari 99 subjek yang dikumpulkan hanya 83 subjek yang memenuhi kriteria inklusi. Hasil sekuensing memperlihatkan bahwa 59 dari 83 sampel dianalisa untuk identifikasi SNP. Kami menemukan 5 SNP nonsynonymous yaitu pada titik G698S, M908L,Y976F, L1076F, dan K1261E.Kata kunci: Plasmodium vivax, Single Nucletide Polymorphism, Gen pvmdr1, Mutasi